1996
DOI: 10.1038/ng1096-218
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and brain abnormalities in mice lacking the Otx1 gene

Abstract: The morphogenesis of the brain and the differentiation of the neural structures are highly complex processes. A series of temporally and spatially regulated morphogenetic events gives rise to smaller areas that are phylogenetically, functionally and often morphogenetically different. Candidate genes for positional information and differentiation during morphogenesis have been isolated. Both in vivo inactivation in mice and impairment in human diseases revealed, that they are required in regional specification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(183 citation statements)
references
References 20 publications
5
173
0
1
Order By: Relevance
“…Animals heterozygous for a loss-of-function mutation of otx2 show abnormalities in the anterior portion of the embryo, including dislocation of the retina and the loss of the lens (50). This eye phenotype, however, is likely to be a secondary effect, resulting from a deformity of the entire rostral region, as the homozygous otx2 mutants exhibit loss of both the fore-and midbrain (50)(51)(52). six3, a murine homolog of the sine oculis gene in Drosophila, is reported to be specifically expressed in the most anterior ridge region of the forebrain (22), which will give rise to derivatives of the nonneural ectoderm.…”
Section: Discussionmentioning
confidence: 99%
“…Animals heterozygous for a loss-of-function mutation of otx2 show abnormalities in the anterior portion of the embryo, including dislocation of the retina and the loss of the lens (50). This eye phenotype, however, is likely to be a secondary effect, resulting from a deformity of the entire rostral region, as the homozygous otx2 mutants exhibit loss of both the fore-and midbrain (50)(51)(52). six3, a murine homolog of the sine oculis gene in Drosophila, is reported to be specifically expressed in the most anterior ridge region of the forebrain (22), which will give rise to derivatives of the nonneural ectoderm.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic studies have revealed that some mouse mutants, such as Otx1 (Acampora et al 1996), Ecl (Cryns et al 2004), Whl (Alavizadeh et al 2001), Obt, Todo, Dz, Cyn, Edy, Mt, and Lda (Kiernan et al 2002), and Crsl and Whi (Hawker et al 2005), show gross changes in the bony semicircular canals. In contrast, others, such as stargazer (Khan et al 2004), het (Paffenholz et al 2004), isk (Vetter et al 1996), tlt and mlh (Hurle et al 2003), Pmca2 (Kozel et al 1998), shaker/waltzer (Sun 2001), and hscy (Longo-Guess et al 2005), have not been reported as having significant bony abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dlx5, which is expressed in the dorsal side of the otic vesicle, is required for the formation of the semicircular canals (Acampora et al, 1999;Depew et al, 1999). Otx1, which is expressed in the ventral side, is needed for the correct morphogenesis of the cochlea (Acampora et al, 1996). The establishment of such a gene expression profile in the otic vesicle, orchestrated by networks or cascades of transcription factors, is essential for inner ear development.…”
Section: Establishment Of Otic Vesicle Patterning By Six1mentioning
confidence: 99%